E-Culture Design in Batubara District by Implementing Web-Based Crowdsourcing Methods - Fauzia Mahyarani; Samsudin (Universitas Medan Area, 2023)
The development of technology today is very rapid and makes it easier for humans to access various information that they want to know by using technology in the form of the internet. E-Cultural is a cultural digitization system that utilizes internet technology to increase efficiency in the field of culture, especially in terms of documentation, dissemination of information as well as knowledge of elements of culture. At this time, web-based information regarding tourism and culture of Batubara Regency is not yet available, the public can only introduce it through social media such as Facebook, Instagram and other media. Lack of legal media at the Batu Bara District Youth, Sports and Culture Service and Tourism to promote tourism and culture in the Batubara District. This prompted the author to create a legal system so that the Batubara Regency Cultural Sports Youth Service can promote tourism and culture by involving the global community. Therefore, this research uses the crowdsourcing method, namely that there is unlimited involvement and regardless of background for everyone who wants to make a contribution, whether paid or free. In the system that I will create, the global community can play a role in updating data or information on the website as well as using the waterfall development method, namely analysis, design, implementation and testing. The results of the development of E-Culture in Batubara Regency using the crowdsourcing method have had a good impact, by making it easier for the local community to promote culture and tourism in their area